POLYHEDROSIS BIOINSEKTISIDA NUCLEAR TEST VIRUS TO SOME SUGAR CANE CROP PEST IN LABORATORY - Enda Lesmana; Irna Syofia; Efrida Lubis (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Research aims to determine the effectivenes of the type for biopesticide Nuclear Polyhedrosis Virus of same major pestof surgacane in laboratory. This research used complety random design (RAL) non factorial with 9 treatments and 3 replication : N0 :  (control)  10  Praghmatocea castanae Hubner, N1 : HaNPV 3 g/l and 10 Phragmatocea castanae Hubner, N2 : SlNPV 3g/l and 10  Phraghmatocea castanae Hubner, N3 : (control)  10  Chilo auricilius, N4 : HaNPV 3 g/l and 10 Chilo auricilius, N5 : SlNPV 3g/l and 10 Chilo auricilius, N6 : (control)  10  Chilo sacchariphagus, N7 : HaNPV 3 g/l and 10 Chilo sacchariphagus , N8 : SlNPV 3g/l and 10  Chilo sacchariphagus.The result of this study indicate that the observation 2 – 14 days after aplication of the precentage of the highest larva mortality in the treatment N5 is equel to 96,67 % in the treatment of Chilo auricilius with3 gr SlNPV/l , Chilo sacchariphagus mortality highest in treatment N8 3gr/l SlNPV of 86,6% Phargmatocea castanae highest precentage of mortality in the treatment  N1 3 gr/l HaNPV reached 60%Keywords: Pest, BioPesticide, Phragmatocea castanae, Chilo auricilius, Chilo sacchariphagus